2013
DOI: 10.2106/jbjs.k.01116
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bone Lavage on Femoral Cement Penetration and Interface Temperature During Oxford Unicompartmental Knee Arthroplasty with Cement

Abstract: Pulsed lavage leads to an increased femoral cement penetration without the risk of heat necrosis at the bone-cement interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 26 publications
0
22
1
1
Order By: Relevance
“…27 Thorough pulsatile lavage should be performed and cement should be pressurised into the central peg hole and multiple anchorage holes should be drilled into the sclerotic bone to facilitate penetration of the cement. 13,27 In order to create a reproducible experimental setup, we did not simulate adverse conditions such as poor cementing technique, or inaccuracies in the posterior saw cut. However, it may be that differences in stability between the two designs only become apparent in adverse conditions: this may be a subject for future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Thorough pulsatile lavage should be performed and cement should be pressurised into the central peg hole and multiple anchorage holes should be drilled into the sclerotic bone to facilitate penetration of the cement. 13,27 In order to create a reproducible experimental setup, we did not simulate adverse conditions such as poor cementing technique, or inaccuracies in the posterior saw cut. However, it may be that differences in stability between the two designs only become apparent in adverse conditions: this may be a subject for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…12 Loosening is a result of mechanical failure at the interface between the cement and either the bone or the component. 13 In 2003, a new design of femoral component was introduced for the cemented Oxford UKR (OUKR, Biomet Ltd, Bridgend, UK). In an attempt to improve the primary stability of the component, this design included an additional peg placed anterior to the existing peg.…”
mentioning
confidence: 99%
“…87 High-pressure pulsatile lavage may have potential benefits of being time saving and effective for removing necrotic tissue and debris, and may offer better mechanical stability for cemented arthroplasty by allowing better cement penetration in cancellous bone tissue. 88,89 However, concerns exist regarding mechanical damage to the tissues, propagation of bacteria into deeper layers of tissue, and negative influence on healing and new bone formation. 90,91 As for wound closure, there is no strong evidence demonstrating clear superiority of one method of closure over the others.…”
Section: Intraoperative Strategiesmentioning
confidence: 99%
“…Generally below 15 psi (103.4 kPa) and over 35 psi (241.3 kPa) are considered low or high pressure, respectively . High‐pulsatile lavage has been shown to improve cement penetration in cancellous bone and increase mechanical strength at the cement‐bone interface during in vitro studies . In vivo studies have also demonstrated fewer radiolucency zones in follow up X‐rays evaluation .…”
Section: Question 31: Is Irrigation Useful? How Should the Delivery Mmentioning
confidence: 99%